PENGARUH ROI (RETURN ON INVESTMENT) DAN ROE (RETURN ON EQUITY) TERHADAP HARGA SAHAM di CIMB NIAGA PERIODE 2020-2021 - Guna, Rian Adi; Fauzan, Fikri Haiqal Al; Kusumastuti, Ratih (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to examine the effect of ROI (Return on Investment) and ROE (Return on Equity) on share prices at CIMB Niaga during the 2018-2021 period. ROI and ROE are financial metrics used to evaluate a company's financial performance. The stock price reflects the market value of the company and is an important indicator for investors in making investment decisions. This research method uses secondary data in the form of CIMB Niaga's financial statements during the period under study. ROI, ROE, and stock price data were collected and analyzed using descriptive statistical techniques and multiple linear regression. In addition, this study also analyzes the trend of the company's financial performance during the period studied.